Medial temporal lobe cavernous malformation associated with epilepsy misdiagnosed as gastrointestinal disease: A case report - Yangzong Wu; Shuting Hong; Limei Zheng; Xiaoxin Chen; Zhiquan Fan; Qiangwang Wu; Congli Luo (Journal of International Medical Research)
A middle-aged (46 years old) woman had been experiencing recurrent upper abdominal distension, nausea, and belching over a 2-year period. She underwent extensive gastrointestinal evaluations, including endoscopy, chest computed tomography, and abdominal ultrasound; she was diagnosed with chronic gastritis and treated with omeprazole (20 mg bid) and mosapride (5 mg tid) for 1 month, with no symptom relief. For further diagnosis and treatment, she visited The Second Hospital of Longyan in April 2023. Further investigations, including brain imaging and video electroencephalography, revealed medial temporal lobe cavernous malformation associated with epilepsy. She subsequently underwent expanded medial temporal lobectomy for removal of the lesion and the surrounding epileptogenic cortex. Postoperatively, her gastrointestinal symptoms resolved completely. This case highlights the importance of considering medial temporal lobe epilepsy in the differential diagnosis of patients presenting with recurrent, short-duration gastrointestinal complaints that are not resolved with conventional treatments.